Thomas Aquinas and Giles of Rome on the reception of forms without the matter - Trifogli, C (Brill Academic Publishers, 2019)
In a passage of De Anima II, chapter 12 (424a17-24), Aristotle makes a general claim about the senses, which is condensed in the formula that the senses are receptive of the sensible forms without the matter. While it is clear that this formula must play an important theoretical role in Aristotle’s account, it is far from clear what it exactly means. Its interpretation is still a focus of controversy among contemporary scholars. In this article the author presents the exegeses of this formula proposed by the two most authoritative commentators on De anima from the second half of the thirteenth century, namely, Thomas Aquinas and Giles of Rome. Both commentators assume that with this formula and in particular with the qualification “without the matter” Aristotle intends to characterize an “intentional” reception of a form, and to contrast it with a “natural” reception, but they give different accounts of intentionality.